Pachydermodactyly/Knuckle pads/Chewing pads. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
Pachydermodactyly, knuckle pads and cheving pads require a differential diagnosis because all these disorders are responsible for the presence of persistent nodules level with the dorsal aspects of the hands.